Termostabilní alkalická fosfatáza v séru gravidních zen - Nesit, V; Kavka, R; Garcic, A (Ceskoslovenska gynekologie, 1991)
In 310 women with normal pregnancies the exponential character of increase of serum thermostable alkaline phosphatase was assessed in the course of pregnancy; depending on the BDP of the course of pregnancy; depending on the BDP of the foetus according to the equation y (mean) = 0.0207.1.0415x (for x = 21-99 mm) and relation to the stage of pregnancy according to formula y (mean) = 0.0152.1.1176x (for x = 15-41 weeks). The menstruation age of pregnancy was in all instances verified by biometric findings of the first sonographic screening during pregnancy. The values of themostable alkaline phosphatase in serum of 15 pregnant women with hypotrophic foetuses (48 measurements) were only 45.7 +/- 9.9% (mean + s) of the mean physiological levels.
Keywords: gestační stáří; Embryonic and Fetal Development; alkalická fosfatasa; Pregnancy; lidé; Gestational Age; Alkaline Phosphatase; ženské pohlaví; embryonální a fetální vývoj; Humans; Female; těhotenství